IMPLEMENTASI MEDIA INTERAKTIF ASLINE-3 SEBAGAI INOVASI PEMBELAJARAN IPAS UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Laelatul Fitria; Agus Wahyudi; Akhwani; Sunanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low student interest in science learning remains a common problem in elementary schools, characterized by a lack of student engagement and enthusiasm during the learning process. This study aims to analyze the implementation and the effect of using the ASLINE-3 interactive media on increasing students’ interest in learning. This study employed a quantitative approach with a one-group pretest-posttest pre-experimental design. The research subjects were 26 fifth-grade students from Class V-A at SDN Kalirungkut I/264 in Surabaya. Data collection techniques included a questionnaire to measure students’ interest in learning and observation to assess the implementation of the learning process. The data were analyzed using descriptive analysis and N-Gain. The results of the study indicate that the implementation of learning using the ASLINE-3 media was in the “very good” category, with a percentage of 100%. Students’ learning interest increased, as indicated by a rise in the average score from 78.08 to 92.69. The N-Gain analysis result of 0.73 indicates a moderate category (fairly effective). Thus, the use of the ASLINE-3 interactive media has proven effective in increasing students’ learning interest in IPAS instruction and can serve as an alternative for technology-based instructional innovation in elementary schools.